1998
DOI: 10.1098/rspb.1998.0535
|View full text |Cite
|
Sign up to set email alerts
|

Re–examining safety in numbers: interactions between risk dilution and collective detection depend upon predator targeting behaviour

Abstract: Many studies document that individuals visually scan for predators less frequently when in the safety of larger groups. This widely replicated e¡ect has generally been explained in terms of distinct predator detection and risk-dilution e¡ects. We show that a strict distinction between detection and dilution disappears when information about attacks is imperfectly shared (as it is in reality). Furthermore, dilution and detection e¡ects change depending on when during an attack the predator targets a particular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
102
2

Year Published

1999
1999
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 170 publications
(111 citation statements)
references
References 34 publications
2
102
2
Order By: Relevance
“…This dilution of risk corresponds to the logic of an earlier verbal model (Grand & Dill 1999) and assumes early targeting by the predator and no information transfer between foragers (Bednekoff & Lima 1998). Collective detection is probably important for many animal groups.…”
Section: (A) Fixed Groups (I) Predation Decreases With Group Sizementioning
confidence: 99%
“…This dilution of risk corresponds to the logic of an earlier verbal model (Grand & Dill 1999) and assumes early targeting by the predator and no information transfer between foragers (Bednekoff & Lima 1998). Collective detection is probably important for many animal groups.…”
Section: (A) Fixed Groups (I) Predation Decreases With Group Sizementioning
confidence: 99%
“…Predator behaviour has often been omitted from models of vigilance or at least simplified into a single, fixed-risk entity (except see Packer & Abrams 1990;Bednekoff & Lima 1998;Scannell et al 2001). We have shown that although the broad predictions of vigilance theory still hold (decreasing vigilance with increasing group size), by adding a predator that has a choice to make as to which group to attack, some new interesting dynamics are brought to light.…”
Section: Discussionmentioning
confidence: 99%
“…This occurred because the effect of dilution is generally stronger than an incremental change in vigilance rates: i.e. switching to the other group is likely to have a more profound effect on an individual's fitness than altering the cooperative vigilance rate (Bednekoff & Lima 1998;Dehn 1990). The more sensitive the predator is to small differences in prey susceptibility, the greater the adopted vigilance rate tends to be for the prey-of course this only occurs when the prey split into two groups; else the optimal vigilance rate is the same.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, individuals that only benefit from indirect detection may, because of an inappropriate reaction, become preferential targets for the predator [13]. Scanning for predators then becomes a defecting attitude that exposes non-vigilant companions to a higher risk of being targeted [15,16]. Collective vigilance is thus a complex and polymorphous game.…”
Section: Introductionmentioning
confidence: 99%